ANALISIS PENGARUH PERTUMBUHAN EKONOMI, INDEKS PEMBANGUNAN MANUSIA, PENGANGGURAN DAN INFLASI TERHADAP JUMLAH PENDUDUK MISKIN DI PROVINSI SUMATERA UTARA - jusmer sihotang (Fakultas Ekonomi dan Bisnis, Universitas HKBP Nommensen, 2019)
This study aims to analyze the influence of economic growth rate, Human Development Index (HDI), open unemployment rate, and inflation rate to the number of people under poverty line in Province of North Sumatera. This research employs multiple linier regression with Ordinary Least Square (OLS) by using secondary time series data from 2001-2015. The OLS result shown that all independent variables can properly and simultaneously significant in explaining the number of people under poverty line in Province of North Sumatera which is indicated by the high of coefficient of determination (R2) and F-statistic. However individually, only HDI and open unemployment rate that significantly influenced to the number of people under poverty line in Province of North Sumatera. This study indicated that the increased of human development index and decreased of open unemployment rate will be decreasing of number of people in poverty in Province of North Sumatera, vise versa. The policy implications that can be recommended to decrease the number of people under poverty line are to increase the HDI, through improvement of life expectancy index, education index, and income index. The decline of people under poverty line can also done by decreasing the level of open unemployment rate through policies that can expand employment opportunities and promote employment programs.